2016
DOI: 10.5539/jmr.v8n2p69
|View full text |Cite
|
Sign up to set email alerts
|

Stability Characterization of Three Porous Layers Model in the Presence of Transverse Magnetic Field

Abstract: The current study concerns, the effect of a horizontal magnetic field on the stability of three horizontal finite layers of immiscible fluids in porous media. The problem examines few representatives of porous media, in which the porous media are assumed to be uniform, homogeneous and isotropic. The dispersion relations are derived using suitable boundary and surface conditions in the form of two simultaneous Mathieu equations of damping terms having complex coefficients. The stability conditions of the pertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…It should be noted that, in the absence of the periodicity of the magnetic field (ω0), the above equations are similar to those obtained by AlHamdan and Alkharashi …”
Section: Formulation Of the Problemsupporting
confidence: 86%
See 1 more Smart Citation
“…It should be noted that, in the absence of the periodicity of the magnetic field (ω0), the above equations are similar to those obtained by AlHamdan and Alkharashi …”
Section: Formulation Of the Problemsupporting
confidence: 86%
“…They demonstrated that the irrotational shearing stresses have a stabilizing effect in the presence of heat and mass transfer throughout the interface. In addition, AlHamdan and Alkharashi discussed the problem of the stability characterization of three permeable layer models under a magnetic field. In this study, they ignored the stability analysis of a uniform streaming.…”
Section: Introductionmentioning
confidence: 99%
“…This means that the viscosity proportion has a stabilizing influence, particularly for larger wave numbers. The same results correspond to the linear stability studies earlier obtained by Moatimid et al [5], El-Dib and Ghaly [27], and AlHamdan, and Alkharashi [29]. Physically, this stabilizing influence is popular in the casting process, as the aim is to keep the free surface of the liquid quiescent, thus avoiding the entrainment of surface debris.…”
Section: The Nonlinear Stability Methodology Of the Uniform Casesupporting
confidence: 89%
“…In other words, it indicates how straightforwardly a fluid is affected by an induced magnetic field. The findings of the examination of the linear stability of three horizontal finite layers of immiscible fluids in porous media are in good agreement with AlHamdan, and Alkharashi [29].…”
Section: The Nonlinear Stability Methodology Of the Uniform Casesupporting
confidence: 82%
See 1 more Smart Citation